Attitudes and acceptance of vaccination against neglected tropical diseases: A multi-country study in Asia - Li Ping Wong; Hai Yen Lee; Haridah Alias; Farhana Nishat Seheli; Abhishek Lachyan; Di Khanh Nguyen; Jamil Ahmed; Zhijian Hu; Yulan Lin (Human Vaccines & Immunotherapeutics)
This study aims to explore the willingness of individuals to be vaccinated against NTDs in Asian countries and China. Between June and December 2023, an anonymous cross-sectional survey was carried out in five Asian countries alongside China. Overall, 48.4% indicated being somewhat willing and 29.2% expressing extreme willingness to receive NTDs vaccination. High attitude scores (adjusted odds ratio [aOR] = 1.54, 95% confidence interval (CI): 11.35–1.75) was associated with higher willingness to be vaccinated against NTDs. The odds of accepting the NTDs vaccine increased among individuals without occupational exposure to NTDs (aOR = 1.46, 95% CI: 1.27–1.68). Those residing in very clean environments exhibited heightened odds of willingness (aOR = 2.94, 95% CI: 2.10–4.11), whereas individuals in somewhat dirty environments demonstrated reduced odds of willingness (aOR = 0.74, 95% CI: 0.56–0.98) compared to the baseline group (very dirty local environment). Moreover, a higher score in sanitation facilities also correlated with increased odds of willingness to receive the NTDs vaccine (aOR = 1.41, 95% CI: 1.21–1.64). The study highlighted key strategies for improving NTDs vaccine uptake in Asian countries, including China, such as fostering positive attitudes toward the vaccine and enhancing perception of infection risks.